Robust Kalman filtering approach to equalizer design - Gao, Ronghua (2008)
The presented robust Kalman filtering algorithm is implemented in the design of an adaptive Decision Feedback Equalizer (DFE) for a multipath channel. The multipath channels are modeled as tapped-delay-line filters. The robust Kalman filtering techniques are used to track channel responses for the adaptation of the DFE equalizer.